A New Endophytic Fusarium Oxysporum Gibberellic Acid: Optimization of Production Using Combined Strategies of Experimental Designs and Potency on Tomato Growth under Stress Condition. (13th March 2020) - Ben Rhouma, Marwa; Kriaa, Mouna; Ben Nasr, Yosri; Mellouli, Lotfi; Kammoun, Radhouane
Abstract : This study reports the potential of the endophytic fungi identified as a Fusarium oxysporum to produce gibberellic acid (GA3). The GA3 production was confirmed by high performance liquid chromatography. To improve the production of this phytohormone under solid state fermentation (SSF), successive optimization strategies were used. Firstly, Plackett-Burman design was applied for screening medium components and culture condition. Under the optimized condition, GA3 yield (7.14 g/kg) was 2.62-fold higher than by the use of the initial condition (2.72 g/kg). The concentration of the most influential parameters and their interaction were optimized with a Box-Behnken experimental design. The optimized condition led to a 1.14-fold enhancement in GA3 production, reaching 8.16 g/kg. The GA3 crude extract obtained by SSF was then used to study its ameliorative role on adverse salinity effect on tomato plants ( Solanum lycopersicum L.). The interactive effects of different GA3 concentrations were examined on morphological and physiological parameters of tomato plants. The application of GA3 (10 -6 M) under salt stress condition (100 mM) was found to improve growth and physiological parameters including plant height, total chlorophyll, starch, and proline contents. The exogenous application of GA3 is a potent strategy to reverse abiotic stress that affect the agricultural productivity and limit plant growth and yield.